2008
DOI: 10.1177/1545968308317699
|View full text |Cite
|
Sign up to set email alerts
|

Task-Evoked BOLD Responses Are Normal in Areas of Diaschisis After Stroke

Abstract: Objective. Cerebral infarction can cause diaschisis, a reduction of blood flow and metabolism in areas of the cortex distant from the site of the lesion. Although the functional magnetic resonance imaging (fMRI) blood oxygen level dependent (BOLD) signal is increasingly used to examine the neural correlates of recovery in stroke, its reliability in areas of diaschisis is uncertain. Design. The effect of chronic diaschisis as measured by resting positron emission tomography on task-evoked BOLD responses during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Consequently, these changes may have only a minimal effect on the signal. This conclusion is further supported by literature suggesting that altered HDRs are not observed in diaschesis [19], which is a condition characterized by loss of function in a portion of the brain that is distant from the lesion.…”
Section: Discussionsupporting
confidence: 82%
“…Consequently, these changes may have only a minimal effect on the signal. This conclusion is further supported by literature suggesting that altered HDRs are not observed in diaschesis [19], which is a condition characterized by loss of function in a portion of the brain that is distant from the lesion.…”
Section: Discussionsupporting
confidence: 82%
“…The BOLD responses were minimally affected in areas of chronic diaschisis. For the patients in this study, the mechanism underlying the BOLD signal, which includes a mismatch between neuronally driven increases in blood flow and a corresponding increase in oxygen use, appeared to be intact in areas of chronic diaschisis (Fair et al, 2009). …”
Section: Participant Variables: Inclusion and Exclusion Criteriamentioning
confidence: 74%
“…Some investigators have demonstrated significant reductions in resting activity in structurally intact regions homologous to the site of damage using positron emission tomography (24) and magnetoencephalography (25), as well as decreases in EEG coherence throughout the lesion hemisphere (26) and across the entire brain (27). One study, however, found that whereas resting PET activity showed significant decreases at a distance from the lesioned site, task-evoked BOLD signal was minimally affected (24).…”
Section: Discussionmentioning
confidence: 98%